The analysis of Ethiopian traditional music instrument through indigenous knowledge (kirar, masinko, begena, kebero and washint/flute) - Sinshaw, Girmaw Ashebir (International Journal of Scientific Research and Management (IJSRM), 2020)
Abstract: This article aims to explore and analytics about Ethiopian traditional music instrument through indigenous knowledge (kirar, masinko, Begena, kebero and washint/flute). The researcher would have observation and referring the difference documentations. Kirar, and masinko are mostly have purposeful for local music including washint, the others which is Kebero, Begena have use full in the majority time for church purpose. Ethiopia has extended culture, art and indigenous knowledge related to original own music. Their studies have qualitative research design that has descriptive methodology to more exploring the traditional music’s free statement descriptions.  Its researcher mainly has providing the descriptive information about the Ethiopian traditional music instrument as analytical finding out.